Barriers to sustainable urban stormwater management in developing countries: The case of Brazil - Vasconcelos, Anaí Floriano; Barbassa, Ademir Paceli; dos Santos, Maria Fernanda Nóbrega [UNESP]; Imani, Maryam Astaraie (Elsevier, 2022)
Urban stormwater management is one of the key challenges concerning sustainability in urban areas. Sustainable urban stormwater management (SUSM) has been increasingly adopted around the world and proved its effectiveness in enhancing sustainability and quality of life in cities. Nevertheless, these strategies are yet to be widely adopted in developing countries. This paper presents barriers to the widespread adoption of SUSM in Brazil, as a developing country case study with severe urban stormwater management problems. To achieve this objective, a thorough review of literature on the barriers has been conducted. An online survey has been designed and disseminated to different Brazilian participant stakeholder groups (i.e. public professionals, private professionals, teachers, and population) to identify the SUSM-related barriers in Brazil. The reviews recognized 31 potential barriers in literature which were categorized into six barrier types. Five of the evaluated barriers have been recognized by at least 80% of the respondents as the most important, namely: “Lack of design and maintenance standards”, “Lack of long-term planning”, “Lack of dissemination and knowledge”, “Lack of incentives”, and “Reluctance to change”. The barriers identified by this research are coherent with the SUSM adoption context in Brazil. These barriers are mainly related to knowledge about SUSM and similar to those diagnosed in previous studies in literature. Overcoming the common barriers is the prelude to effective SUSM solutions to increase urban stormwater sustainability in Brazil and in other developing countries. This paper also presents some initiatives adopted around the world to overcome these barriers, which could be used as reference to an effective public policy proposition.
Keywords: Barriers; Brazil; Runoff source control measures; Stormwater; Sustainable urban stormwater management; Urban sustainability